La Nochebuena south of the border - Rice, James; Smith, Ana (Gretna, La. : Pelican Pub. Co., 1993)
In this bilingual version of "The Night before Christmas," Santa has become Papa Noel and his reindeer have been replaced with eight burros pulling a cart.
In Spanish and English
74140
Keywords: Santa Claus -- Juvenile poetry; Christmas -- Juvenile poetry; Children's poetry, American; Christmas -- Poetry; American poetry; Narrative poetry; Spanish language materials -- Bilingual; Navidad -- Poesia; Bilingual books -- English-Spanish.